Legal Pluralism in Ethiopia Actors, Challenges and Solutions - Epple, Susanne; Assefa, Getachew (Kultur und soziale Praxis, 2020)
Being a home to more than 80 ethnic groups, Ethiopia has to balance normative diversity with efforts to implement state law across its territory. This volume explores the co-existence of state, customary, and religious legal forums from the perspective of legal practitioners and local justice seekers. It shows how the various stakeholders' use of negotiation, and their strategic application of law can lead to unwanted confusion, but also to sustainable conflict resolution, innovative new procedures and hybrid norms. The book thus generates important knowledge on the conditions necessary for stimulating a cooperative co-existence of different legal systems.